Adoption and Implementation of IT Governance: Cases from Australian Higher Education - Bhattacharjya, Jyotirmoyee; Chang, Vanessa (Australasian Association for Information Systems, 2006)
Over the past decade, IS/IT governance has become a key issue of concern for senior IT decision makers around the world. The underlying goals for adopting formal IT governance practices are improvement of business performance and conformance with regulations. This exploratory study examines and compares how IT governance is implemented through a number of structures, processes, and relational mechanisms in two Australian institutions of higher education and how the adoption of industry best practice frameworks such as COBIT, ITIL and ISO17799 have been utilized in the implementation. The study reveals a number of important findings in the context of the implementation of IT governance in the higher education environment. The relationship between IT governance adoption and implementation and business benefit issues are also discussed in the paper.